Hubungan antara Budaya Organisasi dengan Kepuasan Kerja Guru Honorer SD Negeri di Kecamatan Pulogadung Jakarta Timur - Siti Annisa; Neti Karnati; Heru Santosa (Universitas Negeri Jakarta, 2017)
This research aims to determine the relationship between organizational culture and job satisfaction of honorary teacher Elementary School in district Pulogadung East Jakarta. This research is quantitative with two variables, namely: (X) Organizational culture as the independent variable and (Y) job satisfaction as the dependent variable. The research method used is survey method with the correlational studies and quantitative approaches. Samples were as many as 73 honorary teachers. Sampling technique using simple random sampling by the formula Slovin and data collection using questionnaires. From the results of hypothesis testing, obtained tcount = 6.38, which means bigger than ttable = 1.9939. Thus it can be said that the hypothesis can be received. It means null hypothesis (Ho) is rejected. Organizational culture contributed 36.46% to the job satisfaction of honorary teacher Elementary School in District Pulogadung East Jakarta. Based on the results of the research note that the increasingly strong organizational culture, then the higher job satisfaction of honorary teacher Elementary School in District Pulogadung in East Jakarta. It can be concluded that there is a positive relationship between organizational culture and job satisfaction of honorary teacher Elementary School in district Pulogadung East Jakarta.